Frequency
Scott A. Yost
University of Tennessee
The purpose of this note is to calculate the eect of the spring mass on
the oscillation frequency. The goal is to nd the limitations and extensions to
the rule that 1/3 the mass of the spring should be added to to the mass of
the hanging object. This calculation was prompted by a student laboratory
exercise in which it is often seen that the frequency is somewhat lower than
this rule would predict.
Consider a mass M hanging from a spring of unstretched length l, spring
constant k, and mass m. If the mass of the spring is neglected, the oscillation
frequency would be =
_
k/M. The quoted rule suggests that the eect of
the spring mass would be to replace M by M + m/3 in the equation for .
This result can be found in some introductory physics textbooks, including, for
example, Sears, Zemansky and Young, University Physics, 5th edition. The
derivation assumes that m M and the spring oscillates in phase. This note
will keep the assumption about oscillating in phase, but examine more general
cases for the masses.
Let the positions along the unstretched spring be labeled by x, running
from 0 to L, with 0 at the top of the spring, and L at the bottom, where the
mass M is hanging. When the spring is stretched, label the corresponding
positions by a function y(x). The motion of the spring will be described by
the time variation of y. The length of the stretched spring will be denoted
Y = y(L). The top of the spring is xed, at y(0) = 0. It will be assumed that
the spring oscillations are not so large that they cause the spring coils to bump
into each other, so the motion is just determined by the elastic extension and
compression of the spring.
We begin with the derivation of the wave equation for the spring, which is
a wellknown result, and then incorporate the boundary condition describing
the motion of the hanging mass.
Consider a tiny element dx of the spring, which stretches to a length dy.
Scaling the spring constant down from the whole spring to just the element
dx gives the spring constant for just the length dx to be kL/dx. (The spring
1
constant of a spring is inversely proportional to its length.) The change in
length of this element is dy dx. Therefore the tension on this element is
T(x) =
kL
dx
(dy dx) = kL
_
dy
dx
1
_
. (1)
Note that if the stretching were linear, then dy/dx = Y/L + 1, so that the
tension T(x) would reduce to k(Y L), as expected.
The element dx has mass mdx/L, and is acted on by its weight, plus the
dierence in tension on the two ends, giving a total force
dF(x) =
mg
L
dx + (T(x + dx) T(x)) . (2)
The acceleration is y, so Newtons law for the element may be written using
(1) as
dF(x) =
mg
L
dx + kL
d
dx
_
dy
dx
1
_
dx =
_
m
L
dx
_
y. (3)
This may be written as
y
kL
2
m
y
= g, (4)
which is the wave equation for the spring. The general solutions are traveling
waves with velocity L
_
k/m, subject to boundary conditions to be described.
Equation (4) applies to any point on the spring except x = L, where the
additional mass M is hanging. There, the force is
F(L) = Mg T(L) = Mg kL(y
mgx
2
2kL
2
. (8)
2
The required derivatives of y are then
y
(x, t) = 1 +
g
kL
(M + m)
mgx
kL
2
+ u
(x) cos(t),
y
(x, t) = u
(x) cos(t)
mg
kL
2
, (9)
y(x, t) =
2
u(x) cos(t).
Equation (4) then gives
u
(x) =
m
2
kL
2
u(x). (10)
The boundary condition (6) may be expressed in terms of u as
M
2
u(L) cos(t) = kLu
(L)cos(t). (11)
Since the top of the spring doesnt move, u(0) = 0, and the solution to (10)
must take the form
u(x) = a sin(x). (12)
with = (m/k)
1/2
/L. Substituting this solution into (11) gives, at x = L,
tan(L) =
kL
M
2
=
_
m
M
(13)
where
0
=
_
k/M is the oscillation frequency neglecting the mass of the
spring. If we express the mass ratio as = m/M, then the equation for the
dependence of the frequency on the mass becomes
tan
_
1/2
0
_
=
1/2
. (14)
The solution to (14) makes use of the fact that we can write
x
tan(x)
= 1
x
2
3
(x
2
) (15)
where (x) can be expanded in terms of Bernoulli numbers,
(x) =
k=2
2
2k
B
2k

(2k)!
x
k
=
x
2
45
+
2x
3
945
+
x
4
4725
+ ... (16)
or in terms of the Riemann zeta function,
(x) =
2x
2
k=0
(2k + 4)
_
x
2
_
k
. (17)
3
In terms of the function (x), equation (14) may be rewritten as
2
0
=
1 (
2
/
2
0
)
1 + /3
(18)
Equation (18) can be solved iteratively, leading to the result that =
_
k/M
Much more than documents.
Discover everything Scribd has to offer, including books and audiobooks from major publishers.
Cancel anytime.